Association between temporomandibular disorders and abnormal head postures - Faulin, Evandro Francisco (2015)
This study examines the possible correlation between the prevalence of temporomandibular disorders (TMD) and different head postures in the frontal and sagittal planes using photographs of undergraduate students in the School of Dentistry at the Universidade de Brasília - UnB, Brazil. In this nonrandomized, cross-sectional study, the diagnoses of TMD were made with the Research Diagnostic Criteria (RDC)/TMD axis I. The craniovertebral angle was used to evaluate forward head posture in the sagittal plane, and the interpupillary line was used to measure head tilt in the frontal plane. The measurements to evaluate head posture were made using the Software for the Assessment of Posture (SAPO). Students were divided into two study groups, based on the presence or absence of TMD. The study group comprised 46 students and the control group comprised 80 students. Data about head posture and TMD were analyzed with the Statistical Package for the Social Sciences, version 13. Most cases of TMD were classified as degenerative processes (group III), followed by disk displacement (group II) and muscle disorders (group I). There was no sex predominance for the type of disorder. No association was found between prevalence rates for head postures in the frontal plane and the occurrence of TMD. The same result was found for the association of TMD diagnosis with craniovertebral angle among men and women, and the group that contained both men and women. Abnormal head postures were common among individuals both with and without TMD. No association was found between head posture evaluated in the frontal and sagittal planes and TMD diagnosis with the use of RDC/TMD.